The Distribution of Children's Inheritance in the Islamic Law and Custom Law’s Perspective - Hasnah Aziz (International Journal of Law Reconstruction, 2023)
The families who leave the world forever, especially the parents of children, will leave an inheritance, but inheritance becomes a problem of disputes between children which can cause a rift between blood relatives. This research aims to discuss in legal studies regarding the distribution of child inheritance, as well as discuss the parties entitled to inheritance. The research approach method is in the form of a normative approach to concepts, theory, and law, the research is descriptive analysis in nature, uses library research, and is analyzed using secondary legal materials in the form of books, journals, or laws. The results and conclusions of this study are that the provisions of Islamic inheritance law tend to divide inheritance among as many heirs as possible, by dividing a certain portion among several heirs, while the customary law of distribution is carried out on the principle of harmony on the will of the heirs in a friendly atmosphere.